2017
DOI: 10.18203/2349-3291.ijcp20175055
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in children: incidence, causes in relation to diet pattern and psychosocial aspects

Abstract: Background: The present study was conducted to study the incidence of constipation in children attending the paediatric Op and also to know the bowel pattern in constipated children and normal children with respect to food habits and regarding psychosocial aspect of toileting.Methods: A study was done at Katuri Medical College and Hospital in 654 children with age group of 2-12yr of either sex. Children who fulfilled the ROME III criteria for constipation were analysed for demographic profile, socio-economic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 16 publications
7
16
0
Order By: Relevance
“…Gannikan R et al 18 found increased incidence of functional constipation among male compared to females, similar result was found by khanna et al 4 Present study reveals that maximum number of functional constipation was between 2-5 yrs of age (Table 2). Similar results were obtained by Kokkonen et al 17 (mean age 2.5 yrs), Lorenzo et al 14 (between 2-4 yrs) and Kondepalli et al 5 (57.4% in 2-4 yrs of age). As far as socioeconomic status was concerned majority of children belong to lower socioeconomic group (56.19%) ( Table 2).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Gannikan R et al 18 found increased incidence of functional constipation among male compared to females, similar result was found by khanna et al 4 Present study reveals that maximum number of functional constipation was between 2-5 yrs of age (Table 2). Similar results were obtained by Kokkonen et al 17 (mean age 2.5 yrs), Lorenzo et al 14 (between 2-4 yrs) and Kondepalli et al 5 (57.4% in 2-4 yrs of age). As far as socioeconomic status was concerned majority of children belong to lower socioeconomic group (56.19%) ( Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…As far as clinical presentation was concerned the present study revealed that withholding behavior (42.85%) was present among constipated group. (Table3) Khanna et al 4 in the found withholding behavior in 27.4% while Kondapallics et al 5 noted higher incidence (58.4%). 21.58% of children presented with abdominal pain in our study (Table3) which is quite closer in comparison to study done by khanna et al 4 (18.8%), kokkonen et al 17 (26%), kondepallics et al 5 (30.6%).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations